Dampak Kinerja Keuangan atas Enviroment Social Governance (ESG) Score Pada Perusahaan Terindeks IDX ESG Leader - Vijaya, Diota Prameswari (Jurnal Pendidikan Ekonomi Undiksha, 2023)
Assessment of company performance based on financial information is not sufficient for stakeholders in making decisions. Stakeholders need other information, such as non-financial information, namely economic, enviromental and social aspects contained in sustaiability reports. The aims of this research is to anylize the influence of the ESG Score on the financial performance of companies indexed by the IDX ESG Leader from 2020 to 2022. The number of samples in this research is 39 which was determined using the purposive sampling method. Data was processed using simple linear regression analysis. The results of this research show that the ESG Score influences the financial performance of companies listed on the IDX ESG Leader Index from 2020 to 2022.